2020
DOI: 10.1007/s10584-020-02817-z
|View full text |Cite
|
Sign up to set email alerts
|

The value of climate-resilient seeds for smallholder adaptation in sub-Saharan Africa

Abstract: Climate change is threatening food security in many tropical countries, where a large proportion of food is produced by vulnerable smallholder farmers. Interventions are available to offset many of the negative impacts of climate change on agriculture, and they can be tailored to local conditions often through relative modest investments. However, little quantitative information is available to guide investment or policy choices at a time when countries and development agencies are under pressure to implement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Examples of seed system interventions that increase the resilience of smallholder agricultural production systems include developing adapted crop varieties, and ensuring access to seed of a diversity of crops and crop varieties that are adaptable to different environments [8]. The dissemination of climate resilient seeds at the right time and right price could further be promoted through improved transportation networks and investments in seed bulking and storage facilities, improvement of coverage and quality of extension services, better access to subsidized inputs and improved supply chain networks [9]. Access to new seeds and technologies, however, can be difficult, particularly for resource-poor farmers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of seed system interventions that increase the resilience of smallholder agricultural production systems include developing adapted crop varieties, and ensuring access to seed of a diversity of crops and crop varieties that are adaptable to different environments [8]. The dissemination of climate resilient seeds at the right time and right price could further be promoted through improved transportation networks and investments in seed bulking and storage facilities, improvement of coverage and quality of extension services, better access to subsidized inputs and improved supply chain networks [9]. Access to new seeds and technologies, however, can be difficult, particularly for resource-poor farmers [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Malawi and Tanzania demonstrated the value of climate-resilient seeds for smallholder adaptation in sub-Saharan Africa to climate change with the benefits of adopting resilient seeds ranging between USD$984 million and 2.1 billion from 2020-2050 [98]. For chickpea to have expected impacts and contribute to an economic transformation in the face of climate change and variability, seeds of improved varieties with accompanying integrated crop management technologies must reach farmers and be utilized, and the variety turnover (replacement) rate in farmers' field needs to be significantly improved.…”
Section: Taking Chickpea To the "Last Mile"mentioning
confidence: 99%
“…This is possible through sustainable seed systems and strong extension (agricultural advisory) services. Cacho et al [98] emphasized the benefits of establishing and maintaining a flexible national seed sector with participation by communities in the breeding, delivery, and adoption cycle. A sustainable seed system facilitates access to seeds of improved varieties by farmers.…”
Section: Taking Chickpea To the "Last Mile"mentioning
confidence: 99%
“…There is only limited quantitative information available to guide national investment and policy choices ( Vermeulen et al, 2016 ). Relatively small investments in cultivar development and seed multiplication now can save substantial costs later ( Cacho et al, 2016 ), while the cost may be enormous if investment is delayed in maize breeding and seed systems ( Challinor et al, 2016 ). It seems considerable work remains to be done with respect to the kinds of enabling policies and informational environment needed in different contexts, if adoption of bred cultivars by smallholder farmers at the scales required is to occur in the coming decades.…”
Section: Adoption Impact Risk Assessment and Enabling Policy Envirmentioning
confidence: 99%